Tree Ring Chronology of Meteorological Extremes for Ireland, AD425-1650 - Ludlow, Francis (My University, 2011)
﻿For over thirty years the study of Ireland‘s climate history has benefited from the availability of world class dendrochronological (tree ring) records, developed by Michael Baillie, David Brown and colleagues in Queen‘s University, Belfast, based upon the measurement of annual ring widths on oaks native to Ireland (i.e. the Sessile and Pedunculate Oak). Both species are suitable for the construction of long dendrochronological records because of their longevity, clear annual growth rings and a general absence of missing, partial or false rings that cause difficulties with the construction of chronologies from other species (Baillie, 1982, 1995). Living oaks and the availability of timbers from historic buildings and archaeological sites, and still older subfossil oaks preserved in peat bogs, lake margins and river gravels, means that overlapping chronologies of yearly ring widths from these sources can be successfully anchored to the present and extended into the past. Efforts in chronology construction culminated in 1984 in an unbroken 7,272-year oak chronology for Western Europe, incorporating chronologies from the North of Ireland, Britain and Germany (Pilcher et al., 1984).
Keywords: Dendrochronology; Climate history; Tree ring chronology; Making Ireland; Smart & Sustainable Planet; Climate History; Historical Climatology; Irish History; TREE RINGS; Volcanic Eruptions; dendrochronology; irish annals; Environment and housing